Building bridges: the use of reflective oral diaries as a qualitative research tool. Issue 4 (8th August 2017) - Hewitt, Elizabeth
ABSTRACT: The article is a reflection on the use of an oral diary as a qualitative research tool, the role that it played during fieldwork and the methodological issues that emerged. It draws on a small-scale empirical study into primary school teachers' use of group discussion, during which oral diaries were used to explore and document teacher reflective thinking across time. The paper considers the design of the oral diary tool in this context and how its use created both a window on the developing construction of teachers' ideas about their practice of using group discussion in science and also a space to explore emerging analytical themes. The way in which the regular routine of the oral diary entries helped to make connections between the researcher and the participant and nurture fieldwork relationships is discussed in addition to the limitations of this specific research tool.